Riparian Trees and Its Roles to Water Quality in Niukbaun Springs - Chatarina Gradict Semiun; Yulita Iryani Mamulak; Emilianus Pani; Stefanus Stanis (Universitas Djuanda, 2023)
Riparian trees play an essential role in maintaining the quality of the springs. This research was conducted to determine riparian tree types and water quality in Niukbaun Springs, Kupang district. Tree samples were measured by using the Quadrat Sampling Technique. Meanwhile, water quality measurement included physical, chemical, and microbiological parameters. All data collected were analyzed to determine the Shannon-Wiener diversity index, tree endemism status, and gap analysis (conformance of water quality profiles with water quality standards). The results revealed that there were 11 families consisting of Anacardiaceae, Arecaceae, Bombacaceae, Dendrocnide, Elaeocarpaceae, Euphorbiaceae, Meliaceae, Moraceae, Oxalidaceae, Sapindaceae, and Verbenaceae with a total of 149 individuals. The endemism status of the 15 tree species found was 80% classified as endemic and 20% classified as exotic. From the results of the physical and chemical quality tests of water, it was found that almost all parameters met the water quality standards, except for nickel (dissolved metal), which did not meet the water quality standards. Microbiological test results revealed a type of bacteria with similar characteristics to the bacteria Proteus mirabilis, Klebsiella aerogenes, and E. coli. Human activities impact the diversity of riparian trees and the quality of water in Niukbaun Springs.